HUBUNGAN PERILAKU TENTANG PEMBERANTASAN SARANG NYAMUK DAN KEBIASAAN KELUARGA DENGAN KEJADIAN DEMAM BERDARAH DENGUE DI PUSKESMAS SANGIANG KOTA TANGERANG - seftian saputra; gery vebrian; marki marki (Jurnal Kesehatan, 2019)
Background: Eradication of Mosquito Nests (PSN) is a way of controlling vectors as one of the efforts made to prevent the occurrence of transmission of DHF. The PSN campaign has been promoted by the government in this case the Ministry of Health with 3M's motto.Objective: The purpose of this study was to determine the relationship of behavior about eradicating mosquito nests and family habits with the incidence of dengue hemorrhagic fever in Sangiang Health Center, Tangerang City.Research Method: The type of research used is survey research, with an explanatory type. The population in this study were all households in the work area of ​​Sangiang Public Health Center in Tangerang City, totaling 7473 people. As for the sample in this study were 99 people taken randomly. The analytical technique used is univariate to obtain the characteristics of each demographic and bivariate variables used to determine the relationship between the variables of the study.Results: Based on the results of the analysis known: 1) There is a significant relationship between the behavior of mosquito nest eradication with the incidence of dengue in the work area of ​​Sangiang Health Center, Tangerang City. 2) There is no significant relationship between maintaining mosquito larvae with the incidence of dengue in the Sangiang Health Center in Tangerang City. 3) There was no significant relationship between naps using mosquito nets and the incidence of dengue in the work area of ​​Sangiang Health Center, Tangerang City. 4) There is a significant relationship between hanging clothes with the incidence of DHF in the Sangiang Health Center in Tangerang City. 5) There is no significant relationship between the use of mosquito repellent lotion and the habits of the family in the Sangiang Health Center in Tangerang City.Suggestion: Puskesmas can carry out programs needed to increase community participation in conducting PSN activities.